Actual use of electric vehicle in Pakistan: a moderating role of charging infrastructure - Ahmad, Sheraz; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2024)
Due to air pollution, technological change is needed in the transportation sector as traditional vehicles are the top contributor. Replacing fossil fuel vehicles with electric vehicles can minimize contamination in the air. This study has investigated factors affecting the adoption of electric vehicles with the moderation of charging infrastructure using the extended unified theory of acceptance and use of technology (UTAUT2) with additional factors such as environmental concerns, satisfaction with policies, trust, and charging infrastructure. The data were collected from 300 users through a survey questionnaire in Pakistan. Environmental concerns, price value, hedonic motivation, and habit significantly predict use behavior. Nevertheless, facilitating conditions, effort expectancy, social influence, and satisfaction with incentive policies showed insignificant results while affecting use behavior. The moderating effect of charging infrastructure showed insignificant results.
Keywords: charging infrastructure; Electric vehicles; environmental concern; satisfaction with policies; UTAUT2